Pelatihan Pemanfaatan Mendeley Sebagai Reference Tool Pada Artikel Ilmiah Mahasiswa Pendidikan Akuntansi Unipma - Yusdita, Elana Era; Utomo, Supri Wahyudi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2019)
This dedication aims to train the use of reference tools in scientific articles on Accounting Education students at Universitas PGRI Madiun (UNIPMA) in order to answer the need for publication of scientific papers and to adhere to the ethics of publication. The dedication is carried out to all UNIPMA accounting education students who will graduate in the even semester of the 2018/2019 school year by means of presentation of material, examples, practice, and evaluation of work results. The result is that all students can cite and create automatic bibliography in their respective articles.